Development of a risk-score for pericarditis recurrence in patients with a first episode of acute pericarditis. (14th October 2021) - Lazarou, E; Lazaros, G; Antonopoulos, A S; Imazio, M; Vasileiou, P; Karavidas, A; Toutouzas, K; Vassilopoulos, D; Tsioufis, C; Tousoulis, D; Vlachopoulos, C
Abstract: Background/Introduction: Currently we remain uncertain about which patients are at increased risk for recurrent pericarditis. Purpose: We developed a risk score for pericarditis recurrence in patients with acute pericarditis. Methods: We prospectively recruited 262 patients with acute pericarditis. Patients' demographics, clinical, imaging and laboratory data at presentation, were collected. Patients were followed-up for a median of 51 months (interquartile range 21–71) for recurrence. Variables with <10% missingness were entered into multivariable logistic regression models with stepwise elimination to explore independent predictors of recurrence. The performance of the final model was assessed by the c-index and model's calibration and the optimism corrected c-index were evaluated after 10-fold cross-validation. Results: We identified six independent predictors for pericarditis recurrence i.e., age, effusion size, platelet count (negative predictors) and reduced inferior vena cava collapse, in-hospital use of corticosteroids, and heart rate (positive predictors). The final model had good performance for recurrence, c-index 0.783 (95% CI 0.725–0.842), while the optimism corrected c-index after cross-validation was 0.752. Based on these variables we developed a risk score point system for recurrence (0–22 points) with equally good performance (c-index 0.740, 95% CI 0.677–0.803). Patients with a low score (0–7 points) had 21.3% risk for recurrence, while those with high score (≥12 points) had a 69.8% risk for recurrence (Figure 1). The score was predictive of recurrence among most patient subgroups. Conclusions: A simple risk score point system based on 6 variables can be used to predict the individualized risk for pericarditis recurrence among patients with a first episode of acute pericarditis. Funding Acknowledgement: Type of funding sources: None.